Dampak Covid-19 terhadap Tren Belajar dan Bermain Anak Tingkat Sekolah Dasar di Gampong Beurawe - Rauzana, Nila; Setia Ningsih, Yuni (Jurnal Riset dan Pengabdian Masyarakat, 2021)
The purpose of this study is to know the effect of Covid-19 on the trend of elementary school children learning and playing that recognized by their parents. This research uses case study methods and qualitative research approaches to gain information on the effect of Covid-19 on the trend of playing and learning. For confidentiality identity, respondents were given the initials R1, R2, R3, R4, R5, and up to R20. The interview was conducted by asking the respondents one by one. the results showed that the level of achievement had decreased and there was a new learning trend. Online learning causes students and parents to adapt to this learning model. In addition, playing games on cellphones has also become the most favorite games during this pandemic.